The interpretation of mythologemes in A. Pushkin’s works: psycholinguistic aspect - Яковлєва, Ольга; Iakovlieva, O. V.; Iakovlieva, Olga; Григораш, Вікторія; Hryhorash, Viktoriia; Hryhorash, V. S. (ПП "Фенікс", 2018)
Актуальність статті зумовлена, в першу чергу, тим, що сучасні лінгвістичні дослідження проводяться на міждисциплінарному рівні, який передбачає, зокрема, синтез даних етнолінгвістики, лінгвокультурології, психолінгвістики тощо. В рамках останньої дисципліни актуальною є проблема інтерпретації тексту, в процесі якої і здійснюється найвища міра розуміння. По-друге, актуальною в сучасних лінгвістичних дослідженнях залишається проблема, що пов’язана з теорією загальної картини світу. В Україні такі дослідження проводяться з урахуванням етнічної свідомості як україномовного, так і російськомовного населення. Особлива увага при цьому приділяється традиційним віруванням, обрядам та міфології. Враховуючи вищезазначене, метою даної статті є описання на міждисциплінарному рівні з урахуванням народної міфології, вірувань українців та росіян полісемантики міфологем русалка (мавка) і кіт у поетичних творах О. Пушкіна. Увага звертається на авторські інтерпретації традиційних народних поглядів на русалок, які зберігаються в пам’яті східних слов’ян. Виділяється національна специфіка в міфологічній картині світу російських та українців. Подана інформація буде сприяти формуванню найбільш повного «образу змісту пушкінського тексту». У процесі написання статті автори користувалися методом контекстуально-інтерпретаційного аналізу та методом реконструкції етнічних стереотипів, аналізуючи національні особливості міфологічної картини світу українців і росіян. Результати дослідження можуть бути корисними лінгвістам у процесі інтерпретації текстів А. Пушкіна та при вивченні національної специфіки мовної картини світу слов’янських народів.

The article highlights the fact that at the present stage of the development of linguistics, linguistic and cultural studies are held at an interdisciplinary level that involves the synthesis of data of ethnolinguistics, cultural linguistics and psycholinguistics as well. Within the framework of the last discipline, the problem of interpreting the text is relevant, in the process of which the highest measure of understanding is realized. It is worth noticing that the problem, related to the theory of the picture of the world, remains relevant in the works of the linguists of recent years. In Ukraine, such studies are conducted taking into account not only the peculiarities of the ethnic consciousness of both Ukrainian-speaking and Russian-speaking population, but also traditions, rituals, beliefs and mythology. The aim of the article is to describe at an interdisciplinary level, taking into account the knowledge of folk mythology, as well as the beliefs of the Russians and the Ukrainians, polysemantics of the mythologemes of the Cat and the Mermaid in Pushkin’s works. The attention is paid to the author’s interpretation of knowledge about mermaids, which is preserved in the memory of the Eastern Slavs. The national peculiarity in the mythological picture of the world of the Russians and the Ukrainians is partially identified. The presented information will contribute to the formation of the most complete ‘contents image of the Pushkin’s text’. The authors have used the method of contextual-interpretation analysis and the method of reconstruction of ethnic stereotypes in describing the national features of the mythological picture of the world of the Russians and the Ukrainians. The results of the research might be useful for linguists when interpreting A. Pushkin’s works and researching the national peculiarities of the linguistic picture of the world of different peoples.
Iakovlieva, Olga. The interpretation of mythologemes in A. Pushkin’s works: psycholinguistic aspect / O.Iakovlieva, V. Hryhorash // Одеський лінгвістичний вісник. – 2018. – Вип. 12. – С. 55-60. DOI 10.32837/2312-3192/12/8
Keywords: Research Subject Categories::HUMANITIES and RELIGION; Психолінгвістика; когнітивна картина світу; мовна картина світу; міфологема; ідеологема; пролог; мавка; кіт; Psycholinguistics; Cognitive Picture of the World; Linguistic Picture of the World; Mythologeme; Ideologeme; Prologue; Mermaid; Cat